Model Of Human Resources Management Strategy Of Badan Amil Zakat Nasional - Hadi, Moch Aminudin; ., Ujianto; Sardjono, Sigit (Archives of Business Research, 2018)
The purpose of this study is to obtain external factors and internal factors that affect the human resource management strategy of the National Amil Zakat Agency (BAZNAS) and the important themes that are in it. BAZNAS as a non-profit organization and has the potential to mobilize large funds need to prepare its human resources to run the mandate of Law number 23 Year 2011. This research uses qualitative paradigm and with phenomenology approach strategy. Data collection techniques were conducted by interviewing 9 informants. The interview process was recorder by audio recording device and transcribed. The transciption result are arranged in tabulation based on some specific themes. The model was built with Interpretative Structural Modeling (ISM) approach and supported by strategic assumption of SAST (Strategic Assumption Surfacing and Testing) method. The research finds 66 themes discussed in 6 sections. (1) That external factors consist of: large fund mobilization opportunities, human resource inputs BAZNAS, Zakat Inspiration for prosperity, and political influence in the determination of leadership. Internal factors consist of: modeling approach, human resources management paradigm, Baznas as the top of Zakat building in Indonesia, and Global-Mindset. (2) The dimensions of BAZNAS's human resource management strategy are: Fiqh, digital life style, small model organization, collaboration and partnership, economic sharing principles, leadership in core values and core competencies, and 4 pillars of zakat movement. Zakat movement consists of: da'wah, productivity, sharia economy, and zakat management. (3)The core value of human resources BAZNAS consists of hanif, aqlak al karimah, shiddiq, amanah, fathonah, tabligh, integrity, market oriented, entrepreneurship, understanding the concept of rizki, harokah to zakat, awareness of sharia economy, and values Other Islam. (4) BAZNAS's human resource planning function consisting of: BAZNAS strategic human resource planning, human resource development BAZNAS, and organizational development. (5) The BAZNAS human resource retention and utilization function consisting of employment, performance management, and remuneration. (6) The human resource development function of BAZNAS. The interesting themes of the research findings are: small model organization concept, human resource performance ratio, alternative wage pattern, working relationship with asnaf non amil, environment talenta BAZNAS. The contribution of this research is the development of wage theory for non-profit organization, work relation theory, index to measure amil's performance to the gathering, implementation of human resource management function for BAZNAS in Indonesia, and work relation pattern for asnaf non amil.